Fault analysis in power system using power systems computer aided design - Fortune Chukwuebuka Amanze; Amanze Destiny Josiah (International Journal of Advances in Applied Sciences, 2020)
This work presents a fault analysis simulation model of an IEEE 30 bus system in a distribution network. This work annalysed the effect of fault current and fault voltage in a distribution system. A circuit breaker was introduced into the system to neutralize the effect of the fault. The system was run on a PSCAD software and results were obtained. The system was monitored based on the start time and the end time of the fault and how well the circuit breaker reacts with those times. Fault occurred from 0.100 to 0.300 seconds before it was removed. At the time fault was not applied (i.e. from 0.00 to 0.100 and from 0.300 to 0.72), the circuit breaker was close and became open when fault was applied so as to cut off current flow through the line.The result obtained gave the disruption caused by the fault and the quick response of the circuit breaker in neutralizing it. Results gotten are based on when the circuit breaker is close and no fault is applied and when the circuit breaker is open due to fault. From this work, it was obtained that circuit breakers are very essential in system protection and reliability.